Kebijakan Pemerintah Melalui KPI di Propinsi Banten Dalam Memberikan Izin dan Mengawasi Televisi Lokal Dalam Meningkatkan Kualitas Penyiaran (Studi pada Komisi Penyiaran Indonesia Daerah Provinsi Banten) - Taufiqurokhman Taufiqurokhman; T Warasto; Sulasno Sulasno (Public Administration Journal (PAJ), 2017)
Licensing is the main thing about broadcasting arrangements. In a series of recycling processes broadcast regulation, licensing becomes stages of decision of the state (through KPIs and the Commission) to provide an assessment (evaluation) is a broadcasting institution deserves to be given or appropriate to continue the lease rights on frequency. Regional Indonesian Broadcasting Commission or KPID is an independent state institution in Indonesia established in each province serving as a regulator of broadcasting in every province in Indonesia. KPID is an institution capable of controlling the media, especially concerning Broadcasting Permit. Broadcasting Broadcasting Permit (IPP) is a right granted by KPID to broadcasters to conduct broadcasting. To this day there are seven local private television broadcasters in Banten (1.Untirta TV; 2. Baraya TV; 3. CTV Banten; 4. TV3 Tangerang; 5. CCNC; 6. Carlita TV; 7. CTV Network) which already Broadcasting to obtain broadcasting licenses. The results of the study said that in the level of requirements that must be met by local private television broadcasters to obtain IPP, KPID has performed its duties optimally. KPID is always proactive towards local private television broadcasting institutions especially in guiding to complete the necessary conditions so that local TV in Banten Province can meet the requirements required to manage IPP. However, in the implementation of its role related to the phases of acquisition of IPP, KPID has not played an optimal role in performing its duties and functions. This is because in broadcasting there are still violations by local private TV in broadcasting concerning the content of the cameras. Moreover, in making decisions, KPID local government interference in the form menyiarakan television broadcast which is consistent with the request of local governments, which should KPID can not be intervened by any party considering the Broadcasting Commission is an independent institution. So it can be concluded KPID in general can not perform their duties and functions well.